Analisis Kesetaraan Gender Dalam Konteks Pemilihan Umum - Robertus Wardhana Utama; Tri Susilowati (Perkara : Jurnal Ilmu Hukum dan Politik, 2023)
When issues regarding a democratic constitution and respect for human rights and citizens' rights are specifically conditioned from the perspective of gender equality, they must be observed through the principle of balanced justice between men and women. Talking about gender equality certainly cannot be separated from the equal rights and responsibilities of women, which in their development are starting to be aligned with the rights of men in various areas of life. This research aims to analyze gender equality in the context of general elections. The method used by researchers to conduct this research is the literature review method. The results of the analysis explain that gender justice leads women and men towards equality where equal conditions and status to obtain opportunities and enjoy their rights as human beings so that they are able to play a role and participate in development, politics, economics, social, culture, education, defense and security in enjoying the results of this development. Election laws and political parties open up opportunities for women to be equal to men through this 30% quota. Women's struggle to increase women's representation in the legislature through affirmative action can be done by involving women more actively in political parties. Empowering women in political parties is the first step to encourage equality and justice to be achieved between men and women in the public world in the not too distant future.